Digital Ischemic Loss in Systemic Sclerosis. (1st August 2010) - Marvi, Umaima; Chung, Lorinda
Abstract : Digital ischemic loss is a cause of significant morbidity in patients with systemic sclerosis (SSc). Microvascular disease with intimal proliferation and luminal narrowing of small digital arteries, as well as macrovascular disease with narrowing or occlusion of larger digital arteries, contribute to the perfusion defects involved in digital ischemic loss. Immediate clinical evaluation and treatment are mandatory at the onset of critical digital ischemia to prevent digital loss. Hospitalization for medical therapies including intravenous prostacyclin therapy should be considered for all SSc patients who present with critical digital ischemia. Surgical interventions are typically reserved for patients who fail medical therapies and for those with late stage, necrotic tissue. This paper summarizes the current knowledge regarding the risk factors, pathogenesis, evaluation, and treatment of digital ischemic loss in SSc.